LEVERAGING NEW TECHNOLOGIES IN WEB APPLICATION DEVELOPMENT: A FLUTTER CASE STUDY - Botiraliev Bakhtiyor Bahodirovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract:The evolution of web technologies has radically transformed how businesses and developers approach application development. As the demand for more dynamic, responsive, and visually appealing web applications grows, the choice of technology stack becomes pivotal. This paper explores the impact of Flutter in the realm of web development, detailing its features, benefits, and comparative advantages over traditional frameworks.